Manusia dan Kebudayaan Bugis - Makassar dan Kaili di Sulawesi - Andi Mattulada (Antropologi Indonesia, 1991)
In this article, the author describes the ethnography of the Bugis-Makassar, the largest inhabitants in South Sulawesi. His description includes: the historical background, their social stratification, kinship system, traditional political structure, and folklore. How the Bugis-Makassar elite groups are developed and how their social structure influenced by such development is also discussed by the author. Based on the historical evidences it is revealed that identification of the elite groups which is underlined by nobility, emerged in 15th century. In the period of Dutch colonization, composition of the elite groups changed into: pangreh-praja (government administration official) which subsequently emerged as a new elite group. In the era of independence, the position of elites were mostly occupied by the rulling class and well-educated persons. In the last section, the author explains the sirik an institution which refers to human dignity and self-respect - in relation to the conditioning of Indonesian national culture.